Analisis determinan keputusan pembelian produk mie instan pada masyarakat Kecamatan Susukan - Arifata, Zidna; Rahman, Taufikur (Journal of Management and Digital Business, 2021)
This study aims to determine the effect of halal labels, brands, and prices on purchasing decisions for Mie Sedaap products with purchase intention as a mediating variable. The samples taken were 96 respondents with a purposive sampling technique. The data analysis method used is path analysis. The results show that the halal label variable does not affect purchasing decisions. Variable brand, price, and consumer buying interest significantly positively affect purchasing decisions. Consumer buying interest does not mediate the influence of the halal label on purchasing decisions, while consumer buying interest mediates the influence of brand and price on purchasing decisions.